Across the bridge of sighs: reading a Christian theology of melancholy - Wilson, L.C. (2017)
In this thesis, I will proceed by the examination of exemplary texts in the western Christian understanding of, and engagement with, the concept of chronically melancholic and destructively sorrowful states. I will begin with influential texts from the ancient west and near east, such as The Book of Job, and the Pseudo-Aristotle, that have provided the touchstones and archetypes of the subject throughout – and beyond – the historical period covered, as well as contemporary narratives whose concerns and themes instructively throw salient features of the former icons into high relief. Thereafter, I shall trace these themes and their development through the work of those Christians who have most powerfully and significantly dealt with the concept of melancholy theologically.